Pembiasaan Sholat Sunnah Rawatib Dalam Membangun Karakter Taqwa Santri Putri Di Lingkungan Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Uswatun Hasanah; Endang Ekowati; Sofyan Yahya (Journal on Education, 2024)
The character of piety is important to be developed in school-age adolescents through education, habituation, and role models in their living environment, especially in schools, Islamic boarding schools. This study was conducted at the Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung Islamic Boarding School which aims to determine the implementation of the habituation of students in carrying out the sunnah routine prayers to build piety and to determine what are the supporting and inhibiting factors in the implementation of the habituation of sunnah routine prayers. The type of research used in this study is qualitative research with descriptive design, data collection procedures used are observation, interviews and documentation, for checking and checking the validity of data using social situation update procedures, accuracy and perseverance in research and triangulation, while data analysis techniques through four stages, namely: data collection data reduction, data presentation, and drawing conclusions The results of the study indicate that the habit of performing Sunnah prayers is the most important support in building the character of piety of students at the Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung Islamic Boarding School, A habit of performing Sunnah prayers has been embedded in each individual student because of the existence of Islamic boarding school regulations that require all students to carry out the Sunnah prayers and are assisted by guidance, monitoring and motivation given by the ustad / ustadzah. The supporting factors for the habit of performing Sunnah prayers are full support from the management / ustadzah, good influence from the surrounding environment, good adjustments. The inhibiting factors for the habit of praying sunnah rawatib are the lack of self-awareness of the female queuing to perform sunnah rawatib prayers, the lack of awareness of the administrators to control.